What do conferences do? What is academics' intangible return on investment (ROI) from attending an academic tourism conference?. (2nd January 2018) - Edelheim, Johan R.; Thomas, Kimberly; Åberg, Kajsa G.; Phi, Giang
ABSTRACT: Conferences are funny events. They are self-evident elements of our lives as academics: meetings that occur, often annually; take place in various locations; and involve (hopefully) like-minded people, aiming to share their latest research findings. Conferences are actually so self-evident that very little research exists analysing what takes place at conferences, why people attend them in the first place, and essentially what the conference does to delegates as participants. This article is, on one hand, a reflective report from an academic conference: TEFI 9—Celebrating the Disruptive Power of Caring in Tourism Education . But it is also simultaneously an analysis of the implicit and explicit rationale and return on investment for attending academic conferences, in the words of three, at that time, PhD candidate rapporteurs and one professor rapporteur, who acts as this article's narrator.